Rekonstruksi Pemahaman Hadis Analisis Hadis di dalam Fatwa MUI tentang Kesetaraan Jender - Muhammad Nawir (Qur'an and Hadith Academic Society, 2016)
The paper studies the use of Hadith in the discourse of gender issue reflected in the issuance of MUI’s fatwa. Using descriptive analytic method, it finds that the use of hadiths about gender equality in MUI’s fatwa was based on the validity of the hadith codified by authoritative Hadith scholars. The study confirms Ibnuddin’s (2011), M. Quraish Shihab’s (2003), and Yusuf al-Qarada>wi’s (2011) findings, which say that understanding the Traditions about women requires metaphorical interpretation. This study differs from M. Asrorun Ni'am Saleh’s (2012) which argues that that the MUI’s fatwa on female circumcision is neutral, and from Yunahar Ilyas’s (1997) which shows discrimination.